William H. Masters papers - Masters, William H.; Johnson, Virginia E.
TLS (1971 October 27; St. Louis, Mo.) from Masters to Fred B. Gable and a copy of a letter (1972 December 14; Philadelphia, Pa.) from Gable to the editor of World Magazine concerning the research into sexual behavior conducted by Masters and Virginia E. Johnson. Includes a photograph of Masters and a signed photograph of Johnson.
William Howell Masters, gynecologist, b. 1912; and Virginia E. Johnson, psychologist, b. 1925.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gable, Fred B. -- Correspondence; Sex (Biology); Sex (Psychology); Physicians